Efficiency in Cloud Computing through Serverless and Green Computing based on Microarchitecture - Fahira, Fahira; Awangga, Rolly Maulana; Gopikrishnan, Sundaram (Department of Information Systems and Technology, Faculty of Intelligent Electrical and Informatics Technology, Universitas 17 Agustus 1945 Surabaya, 2024)
PT Pelindo Multi Terminal is a subholding of PT Pelabuhan Indonesia (Persero), a State-Owned Enter-prise (SOE). PT Pelindo Multi Terminal carries out Kesehatan dan Keselamatan Kerja (K3) or Occupa-tional Health and Safety (OHS) monitoring, which currently still uses manual methods with paper. This method causes problems, such as delays in decision making and the inability to monitor events in real-time. This research aims to overcome these problems by proposing an application called